Spontaneous uterine rupture masquerading as intestinal perforation in a primigravida with polyhydramnios - Raut, Shruti; Saravade, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Spontaneous rupture of an unscarred uterus in a primigravida is an exceptionally rare and life-threatening event. We report the case of a 26-year-old primigravida at 36 weeks who was referred as a suspected case of intestinal perforation. Cross-sectional imaging revealed a uterine fundal rent with hemoperitoneum. Intraoperative findings included dense pelvic adhesions, fat stranding, and a ruptured dilated vessel over the uterine rent, suggestive of chronic pelvic inflammation possibly due to endometriosis or prior subclinical pelvic inflammatory disease. This case highlights the importance of considering uterine rupture in unscarred uteri, particularly when atypical presentations occur.